HASSKARLS CINCHONA BARKS 1. HISTORICAL REVIEW - RIDSDALE, C. E.; -, L. A. Anderson. A. T. Keene & J. I). Phi - (Research Center for Biology, 1984)
The preliminary results of alkaloid analyses of Hasskaiis cinchona bark collection, made in Peru in 1852/3 is given, and the identity and historical aspects of the material discussed in respect of the role the plants played in the Javanese plantations.